Investigation of Effects (Welding Sequence, Fixturing, Welding Points) on Distortions after Spot Welding for Determining Individual and Cumulative Tolerances - Yurei, Cem; Akdogan, Anil; Durakbasa, Numan M. (ELSEVIER, 2016)
The manufacturing and GPS (Geometrical Product Specifications and Verification) have to be thought and analysed together. Welding and Metal Forming are two of manufacturing methods, which are used to create sheet metal parts assembly groups. The dimensions do not stay steady and they change during these two manufacturing methods. Because firstly, after forming (for example bending) the springback and secondly, after welding (for example spot welding) the distortions exist. In this study, the distortions after spot welding are researched and their effects on tolerance chain and assembly tolerances are analysed. These distortions are determined with analysis software after designing some sheet metal part assembly examples. After that, these distortions are achieved with real measurement (scanning) after welding of the sheet parts. At the final step, the analysis and measurement results are compared. (C) 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.
Keywords: Statistical Tolerance Analysis Methods; Tolerance Stackup; Distortions; Spot Welding; Welding Sequence; Clamping; Automation & Control Systems